THE EFFECTS OF ENERGY DRINKS ON HEALTH - Khazhimatova Guzal Marufzhanovna (Web of Journals Publishing, 2024)
The literature review highlights the prevalence of energy drinks consumption, and describes their main ingredients (caffeine, taurine, guarana, ginseng, sweeteners). Numerous facts are given that testify to the negative impact on human health (including deaths) of the systematic use of large amounts of these beverages, both independently and in mixture with alcohol. It has been shown that the cardiovascular system, central nervous system and liver are most affected.
Keywords: energy drinks; caffeine; taurine; guarana; human health; ecological factors.